2020
DOI: 10.18632/aging.103435
|View full text |Cite
|
Sign up to set email alerts
|

Lowered levels of nicotinic acetylcholine receptors and elevated apoptosis in the hippocampus of brains from patients with type 2 diabetes mellitus and db/db mice

Abstract: Cognitive impairment caused by diabetes has been gradually recognized. Generally, nicotinic acetylcholine receptors (nAChRs) play an important role in the pathogenesis in dementia disorders including Alzheimer's disease (AD). However, the expression of nAChRs in the brains of type 2 diabetes mellitus (T2DM) is unexplored. This study explored the alterations of nAChRs in the postmortem brains of patients with T2DM and brains of db/db mice. Morris water maze test was used to appraise the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…We first demonstrated that adult db/db mice exhibit impaired spatial learning and recall in the MWM. Our findings are in line with previous reports which have demonstrated that db/db mice present impaired spatial memory in the MWM (Ramos-Rodriguez et al, 2013;Ren et al, 2021;Wang et al, 2021;Xu et al, 2020) (reviewed in Watanabe & Sakamoto, 2021). In our present study, we demonstrate that 3-to 5-month-old T2DM mice exhibit significant impairments in spatial acquisition in the MWM.…”
Section: Discussionsupporting
confidence: 94%
“…We first demonstrated that adult db/db mice exhibit impaired spatial learning and recall in the MWM. Our findings are in line with previous reports which have demonstrated that db/db mice present impaired spatial memory in the MWM (Ramos-Rodriguez et al, 2013;Ren et al, 2021;Wang et al, 2021;Xu et al, 2020) (reviewed in Watanabe & Sakamoto, 2021). In our present study, we demonstrate that 3-to 5-month-old T2DM mice exhibit significant impairments in spatial acquisition in the MWM.…”
Section: Discussionsupporting
confidence: 94%
“…[35] There is a close relationship between the level of BDNF and α7 nAChR in the brain so that the level of both molecules in the brain of diabetic model mice decreases, and consequently, the apoptosis of neurons in the hippocampus increases. [36] In our study, the expression of α7 nAChR increased in the hippocampus of Aβ-P rats in the same way as BDNF. PNU-282987 and GTS-21 (both α7 nAChR agonists) stimulate PI3K/Akt and ERK/CREB signaling and increase BDNF expression.…”
Section: Discussionsupporting
confidence: 67%
“…Additionally, numerous clinical studies have shown that diabetes mellitus is closely related to vascular dementia, as well as Alzheimer’s disease (AD) ( 5 , 6 ). Multiple studies have demonstrated that factors such as neuronal apoptosis, oxidative stress, neuroinflammation and altered neurogenesis may play a role in DCD ( 7 , 8 ), in which oxidative stress and neuroinflammation are early-onset mechanism in diabetic encephalopathy ( 9 , 10 ). The hippocampus plays a vital role in learning and memory, and the impairment of its function is linked to DCD ( 11 ).…”
Section: Introductionmentioning
confidence: 99%